Ein Beitrag zur Nomenklatur der Piesmatidae (Heteroptera: Piesmatidae). - Proeseler, Gerhard (Contributions to Entomology = Beiträge zur Entomologie, 1967)
Previous publications give the name of a species of tingid bugs as either Piesma quadratum Fieber or Piesma quadrata Fieber. Since the Greek word Piesma is of neuter gender and the gender of the name of the species must correspond to that of the name of the genus, only the first name (P. quadratum) is correct. Consequently, it must also be Piesma capitatum Wolff and P. maculatum Lapp. Since 1958 the names of the seven American species belonging to the family Piesmatidae have always been given with neuter gender.